Modified Alizarin Red S-Alcian Blue Staining for Reptilian Skeleton - Muhammad Ja’far Luthfi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2016)
Skeletal staining is an important method in anatomical study. The aim of the research was to develop staining and clearing method of Reptilian skeleton using Alizarin Red S-Alcian Blue. The specimen were eviscerated, fixed, stained, cleared, and keep in glycerine solution. This modified double-staining has successfully stain bone and cartilage of Reptilian.